2015
DOI: 10.1038/jcbfm.2014.207
|View full text |Cite
|
Sign up to set email alerts
|

Brain Endothelial miR-146a Negatively Modulates T-Cell Adhesion through Repressing Multiple Targets to Inhibit NF-κB Activation

Abstract: Pro-inflammatory cytokine-induced activation of nuclear factor, NF-κB has an important role in leukocyte adhesion to, and subsequent migration across, brain endothelial cells (BECs), which is crucial for the development of neuroinflammatory disorders such as multiple sclerosis (MS). In contrast, microRNA-146a (miR-146a) has emerged as an anti-inflammatory molecule by inhibiting NF-κB activity in various cell types, but its effect in BECs during neuroinflammation remains to be evaluated. Here, we show that miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 45 publications
4
66
0
1
Order By: Relevance
“…These data support the acquisition of a M1 phenotype in microglia activated by LPS with the loss of their neuroprotective properties and sustained upregulation of proinflammatory features by the miR-155 regulation networks. Intriguingly, the overexpression of miR-146a may constitute a mechanism of regulating the inflammatory response [56], exemplifying the complexity of the M1/M2/M0 landscape. In addition, we found that N9 cells were able to release exosomes of approximately 160 nm diameter, as determined by DLS analysis (Figure 7(b)).…”
Section: Resultsmentioning
confidence: 99%
“…These data support the acquisition of a M1 phenotype in microglia activated by LPS with the loss of their neuroprotective properties and sustained upregulation of proinflammatory features by the miR-155 regulation networks. Intriguingly, the overexpression of miR-146a may constitute a mechanism of regulating the inflammatory response [56], exemplifying the complexity of the M1/M2/M0 landscape. In addition, we found that N9 cells were able to release exosomes of approximately 160 nm diameter, as determined by DLS analysis (Figure 7(b)).…”
Section: Resultsmentioning
confidence: 99%
“…Predominantly, miR-146a has been implicated as an epigenetic regulator of inflammatory responses. The regulatory roles of miR-146a that affects inflammatory pathways have been shown in various cell types, including human RPE cells (50), trabecular meshwork cells (51), brain endothelial cells (52), brain microglical cells (53), and cells from intervertebral discs (54). Much work has demonstrated that REC are an important cell type substantially affected in diabetic retinopathy (5557).…”
Section: Discussionmentioning
confidence: 99%
“…HRMECs and human embryonic kidney 293T cells (HEK293T; ATCC) were cultured for endothelial functional assays (migration, proliferation, and tube formation) and luciferase assays, respectively. FAMlabeled premiRNA (Ambion) was used to analyze transfection efficiency of miRNAs (52) and showed around 90% transfection efficiency in HRMECs (SI Appendix, Fig. S9).…”
Section: Methodsmentioning
confidence: 99%